Fabrication of Binder‐Free TiO2 Nanofibers@Carbon Cloth for Flexible and Ultra‐Stable Supercapacitor for Wearable Electronics. (17th May 2022) - Rani, Shalu; Kumar, Nagesh; Sharma, Yogesh
Abstract: For the realization of the miniaturized devices for flexible/wearable electronics systems in the current electronics industry; flexible, safe, and compatible energy storage devices are of great research interest. Herein, carbon cloth (CC) textile is coated by TiO2 nanofibers (NFs) through a safe and facile electrophoretic deposition (EPD) technique for flexible/wearable supercapacitor (SC) application. The modified microstructure of the flexible and binder‐free electrode fabricated via EPD shows a high areal capacitance of 1651 mF cm −2 at 1 mA cm −2 current density. Moreover, the electrode shows the high cyclability with 100% capacitance retention after 15 000 cycles at 10 mA cm −2 current density, presents the ultra‐high stability for the fabricated electrode. Further, a fully flexible symmetric SC device is fabricated utilizing the fabricated electrodes assembled with the gel electrolyte. The device delivers an areal capacitance of 468 mF cm −2 at 1 mA cm −2 current density with 97% capacitance retention after 30 000 successive cycles and 98% retention after 2000 bending cycles at 5 mA cm −2 . Moreover, the SC device delivers the maximum areal energy density and areal power density of 0.14 mWh cm −2 and 3.6 mW cm −2, respectively. Abstract : Binder‐free electrodes of TiO2 nanofibers are fabricated over carbon cloth textile via electrophoretic deposition for flexible, safe, and compatible supercapacitor (SC) in wearable electronics applications. The well‐designed electrode architecture offers enhanced electronic and ionic conduction. The fabricated symmetric SC device shows good electrochemical performance. Two devices connected in series glow 19 red LEDs.